Nobody's story - Gallagher, Catherine (Univ. of California Press, 1994)
Exploring the careers of five influential women writers of the Restoration and eighteenth century, Catherine Gallagher reveals the underlying connections between the increasing prestige of female authorship, the economy of credit and debt, and the rise of the novel. The
Keywords: Burney; Fanny; Lennox; Charlotte; Behn; Aphra; Manley; Mary DeLaRivière; Edgeworth; Maria; Femmes et littérature - Grande-Bretagne - Histoire - 17e siècle; Femmes et littérature - Grande-Bretagne - Histoire - 18e siècle; Femmes et littérature - Grande-Bretagne - Histoire - 19e siècle; Littérature - Édition - Grande-Bretagne - Histoire; Littérature anglaise - Histoire et critique; Littérature féministe - Grande-Bretagne - Histoire et critique; Rôle selon le sexe dans la littérature; Écrits de femmes anglais - Histoire et critique; Écrivaines anglaises - Conditions économiques; Geschichte; Wirtschaft; English literature; Feminism and literature; Literature publishing; Sex role in literature; Women and literature; Women authors; English; Schriftstellerin; Frauenliteratur; Englisch